Tolerance in the Perspective of Surah Al-Kafirun - Azhar (MultiTech Publisher, 2024)
This research discusses focusing on Surah Al-Kafirun and hadis which are relevant in the context of religious tolerance. This surah (Al-Kafirun) was revealed in response to the polytheists' offer to the Prophet Muhammad Saw to alternately worship Allah and their gods, highlighting the importance of the principle of oneness in Islam. Currently, there is disharmony between non-Islamic and Muslim communities, particularly regarding the term